Original sin(s): lessons from the US model of special education and an opportunity for leaders. Issue 5 (3rd May 2020) - Cornett, Jake; Knackstedt, Kimberly M.
Abstract : Purpose: The United States (US) system of special education committed three original sins that perpetuate inequities between children with disabilities and their peers. The purpose of this paper is to examine the history of the US system, contrast this history against international disability law and identify opportunities for leaders to transform policy and practice for inclusive education. Design/methodology/approach: This paper explores the development of the three sins in US special education law: (1) weaving throughout it a medical model of disability, (2) failing to mandate inclusion and (3) hampering meaningful enforcement. The paper contrasts the US system with the United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD), an international law adopted by 180 nations that requires inclusion of people with disabilities at all levels of systems. Findings: This paper finds that the United States has not embraced inclusion in education, but has permitted a continuum of segregation and integration. After a discussion of the three sins and the CRPD, the authors describe opportunities for international and US leaders to learn from the original sins of the United States and develop a system of true inclusion for all students through the transformation of policy and practice. Originality/value: This paper contributes to the literature on policy development and implementation, with implications for future amendments to US education law and international public administration of education.